Exploring administrator perspectives on designing and implementing support and growth plans for underperforming teachers - Jacobo Martinez, Claudia Berenice (My University, 2026)
This interpretive qualitative study explored school administrators’ perspectives on designing and implementing support and growth plans for underperforming teachers. Grounded in social constructivism and informed by Vygotsky’s concepts of the Zone of Proximal Development and the More Knowledgeable Other, the study examined how administrators structure interventions, navigate challenges, and monitor teacher development within accountability-driven systems. The problem addressed was the inconsistent and unclear processes for identifying and supporting underperforming teachers, which may negatively affect instructional quality and student outcomes. Ten campus-level administrators from a large urban district in the southern United States participated in semi-structured interviews, and anonymized support plan documents were analyzed to triangulate findings. Thematic analysis revealed that effective support plans are characterized by clear standards alignment, structured coaching and modeling, ongoing monitoring, and measurable goals. Administrators also described persistent tensions related to time constraints, documentation demands, policy compliance, and teacher resistance. Teacher mindset emerged as a critical factor influencing implementation and outcomes. Findings suggest that support plans function simultaneously as developmental scaffolds and accountability mechanisms. When aligned with relational trust and sustained coaching, they promote instructional growth; when misaligned, they risk becoming procedural exercises with limited impact.
Keywords: Instructional leadership; Underperforming teachers; Teacher support plans; Administrator perspectives; Social constructivism; Zone of Proximal Development; Teacher development; Qualitative research